Supervision Outcomes as Predictor to the Supervisory Relationship and Supervision Contextual Factors: Study on the Internship Trainee Counsellors - Nor Mazlina, Ghazali; Wan Marzuki, Wan Jaafar; Azzahrah, Anuar (EDP Sciences, 2018)
The purpose of this study was to investigate the influence of the supervisory relationship and contextual supervision factors on the supervision outcomes among trainee counsellors. Respondents were 120 trainee counsellors and 18 supervisors from four public universities in Malaysia. Eight instruments were used in measuring the variables. The Supervisory Working Alliance Trainee Inventory (SWAI-T) was administered to measure the supervisory working alliance among trainee counsellors and the Role Conflict Role Ambiguity Inventory (RCRAI) was administered to measure the role conflict among trainee counsellors. Meanwhile, the Supervision Interaction Questionnaire - Supervisee and Supervisor Inventory (SIQ-S) was used to measure the interaction between trainee counsellors and supervisor and the Counsellor Rating Form - Short (CRF-S) was used to measure the characteristics of the supervisors in supervision. The Selective Theory Sorter (STS) inventory was used to measure the counselling orientations among the trainee counsellors and supervisors whereas the Multicultural Counselling Knowledge and Awareness Scale (MCKAS) measures the knowledge and awareness toward multicultural counselling among trainee counsellors. The Supervision Outcomes Survey (SOS) and the Counsellor Performance Inventory (CPI) were utilized to measure the satisfaction and performance among trainee counsellors. Results have revealed that there was a significant correlation between the supervisory relationship (supervisees' working alliance, supervisees' role conflict, supervision interaction, supervisors' attributes) and supervision outcomes, r (118) =.53; p <.05. Other factors that have contributed to the significant correlations of supervision outcomes were supervisees' working alliance, supervisees' role conflict, and supervisors' attributes, r(120) =.55; p <.05; r (120) =.21; p <.05; and r (116) =.50; p <.05 respectively. However, the result has shown that there was no significant correlation between the supervision contextual factors (supervisees' and supervisors' counselling orientation and supervisees' cultural knowledge and awareness) and supervision outcomes. The Multiple Regression analyses reported that the supervisory relationship had an influence on the supervision outcomes, R2 =.28, F (1,105) = 40.2, p <.05. Meanwhile, the supervision contextual factors had no influence on the supervision outcomes. Based on the research findings, the model signified that the supervision process could bring out changes in the supervisees. Practically, the supervisees' working alliance was a significant factor that has influenced the supervisees' development. Therefore, the academic supervisor should consider the supervisees' role conflict, supervision interaction, and supervisors' attributes during supervision. It is recommended that the differences between supervision interaction of the supervisors and the supervisees are to be examined in the future research. © The Authors, published by EDP Sciences, 2018.